2020
DOI: 10.1038/s41593-020-0664-0
|View full text |Cite|
|
Sign up to set email alerts
|

AHR is a Zika virus host factor and a candidate target for antiviral therapy

Abstract: Zika virus (ZIKV) is a flavivirus linked to multiple birth defects including microcephaly, known as congenital ZIKV syndrome. The identification of host factors involved in ZIKV replication may guide efficacious therapeutic interventions. In genome-wide transcriptional studies, we found that ZIKV infection triggers aryl hydrocarbon receptor (AHR) activation. Specifically, ZIKV infection induces kynurenine production, which activates AHR limiting the production of type I interferons involved in anti-viral immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 55 publications
6
85
0
1
Order By: Relevance
“…In this scenario, MAFB and MAF differentially affect the expression of AHR, and an enhanced MAFB/MAF ratio correlates with an increased expression of AHR, as it is also seen in macrophages activated by TLR4 or TLR7 ligands (our transcriptional information in GSE156921). The MAFB/MAF ratio-AHR expression link is of special relevance because AhR is activated during coronavirus infection and the constitutive AhR activation constrains type I IFN-mediated antiviral innate defense (44,45). In fact, a role for AhR in SARS-CoV-2 pathology has been recently proposed (46), and AhR antagonists have been propositioned as potential therapy for coronavirus-infected patients (46).…”
Section: Mafb and Maf Control Gene Expression In Pulmonary Macrophagementioning
confidence: 99%
“…In this scenario, MAFB and MAF differentially affect the expression of AHR, and an enhanced MAFB/MAF ratio correlates with an increased expression of AHR, as it is also seen in macrophages activated by TLR4 or TLR7 ligands (our transcriptional information in GSE156921). The MAFB/MAF ratio-AHR expression link is of special relevance because AhR is activated during coronavirus infection and the constitutive AhR activation constrains type I IFN-mediated antiviral innate defense (44,45). In fact, a role for AhR in SARS-CoV-2 pathology has been recently proposed (46), and AhR antagonists have been propositioned as potential therapy for coronavirus-infected patients (46).…”
Section: Mafb and Maf Control Gene Expression In Pulmonary Macrophagementioning
confidence: 99%
“…AHR activation by metabolites produced by tumors 14,15 or in the context of viral infection 16 interferes with the generation of protective immunity. Indeed, AHR suppresses the production of type I interferons (IFN-I) 17,18 , probably as part of a feedback negative mechanism because IFN-I induce AHR expression 19 . We recently showed that AHR activation during the infection with Zika or dengue virus suppresses IFN-I-dependent and IFN-I-independent anti-viral innate and intrinsic immunity 17 .…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
“…Indeed, AHR suppresses the production of type I interferons (IFN-I) 17,18 , probably as part of a feedback negative mechanism because IFN-I induce AHR expression 19 . We recently showed that AHR activation during the infection with Zika or dengue virus suppresses IFN-I-dependent and IFN-I-independent anti-viral innate and intrinsic immunity 17 . Most importantly, an AHR antagonist optimized for human use boosted anti-viral immunity, interfered with viral replication and ameliorated multiple aspects of Zika congenital syndrome including microcephaly in animal models 17 , identifying AHR as a candidate target for therapeutic intervention.…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the aryl hydrocarbon receptor (AHR) is activated during coronavirus infections, impacting antiviral immunity and lung cells associated with repair [40]. Signalling via AHR may dampen the immune response against coronavirus [41]. It has been reported that although some signalling is needed for coronavirus replication, excessive activation of this pathway may be deleterious for the virus.…”
Section: Ahr and Viral Infectionsmentioning
confidence: 99%